2020
DOI: 10.1038/s41467-020-17796-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and cytopathic effect of SARS-CoV-2 infection in human airway epithelial cells

Abstract: SARS-CoV-2, a β-coronavirus, has rapidly spread across the world, highlighting its high transmissibility, but the underlying morphogenesis and pathogenesis remain poorly understood. Here, we characterize the replication dynamics, cell tropism and morphogenesis of SARS-CoV-2 in organotypic human airway epithelial (HAE) cultures. SARS-CoV-2 replicates efficiently and infects both ciliated and secretory cells in HAE cultures. In comparison, HCoV-NL63 replicates to lower titers and is only detected in ciliated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
318
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(389 citation statements)
references
References 32 publications
45
318
1
2
Order By: Relevance
“…It is curious that secretory goblet and club cells behave in opposite ways to SARS-CoV-2 infection, since both of these cell types are surface epithelial cells accessible on the airway lumen (38). The permissibility of goblet cells to SARS-CoV-2 infection was previously reported by immunochemistry staining of biopsy airway section specimens from COVID-19 patients (36), as well as being supported by a recent in vitro modeling of HAE (34). Club cells express the viral receptor ACE2, but at a lower level than goblet, ciliated, and basal cells (43) (see Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is curious that secretory goblet and club cells behave in opposite ways to SARS-CoV-2 infection, since both of these cell types are surface epithelial cells accessible on the airway lumen (38). The permissibility of goblet cells to SARS-CoV-2 infection was previously reported by immunochemistry staining of biopsy airway section specimens from COVID-19 patients (36), as well as being supported by a recent in vitro modeling of HAE (34). Club cells express the viral receptor ACE2, but at a lower level than goblet, ciliated, and basal cells (43) (see Fig.…”
Section: Discussionmentioning
confidence: 69%
“…This in vitro model of human airway epithelium (HAE) cultured at an ALI (HAE-ALI) closely recapitulates many important characteristics of respiratory virus-host cell interactions seen in the infected upper and lower airways in vivo and has been used to study many human respiratory viruses (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including SARS-CoV (30,31). Primary HAE-ALI can be infected by SARS-CoV-2 (32,33), resulting in epithelial damage (34), and they can be used for virus isolation (1,16). Notably, differentiation at an ALI results in a drastic increase in expression and the polar presentation of the viral receptor angiotensin-converting enzyme 2 (ACE2) (2,35) on the apical membrane (30,31).…”
mentioning
confidence: 99%
“…This model also demonstrates key aspects of host antiviral epithelial immunity [8, 9]. Recently, several studies using primary human lung cell cultures and respiratory cells isolated from SARS-CoV-2 infected patients have identified SARS-CoV-2 tropism for ciliated and secretory cells in the upper airway [10-13]. However, the heterogeneity of virus replication and induction of antiviral genes and proinflammatory cytokines within these cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 can simultaneously infect ciliated cells and secretory cells of human respiratory epithelium. Therefore, compared with common coronaviruses, it is more infectious and pathogenic [3] . As of August14, 2020 (03:37 pm CEST), the WHO website reported that there were 89,625 con rmed cases in China, of which 4,707 patients died.…”
Section: Introductionmentioning
confidence: 99%